PENGARUH DISIPLIN KERJA DAN KOMPETENSI TERHADAP KINERJA GURU DENGAN MODERASI BUDAYA SEKOLAH DI MTs SWASTA SE KKMTs N MARGOYOSO KABUPATEN PATI - Ahmad Ruman Masyfu’, 1252020003; Basiya, R. (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to examine and analyze the influence of disciplinary, competence on the performance by moderated school culture that takes an object of junior high school teachers in Margoyoso subdistrict. Sampling was done by proportional random sampling technique. From the result of proportional random sampling, the sample was used in this study, totaling 253 people. Testing data technique which is used in this study include validity test by factor analysis, reliability test by Cronbach alpha formula, multiple regression analysis, and significanceÂ  tests, the coeffisien of determination to prove the hypothesis and moderated test. The result showed that the variables of school culture proved to moderate the effect of discipline on the performance of junior high school teachers in Margoyoso subdistrict Pati regency. Discipline and school culture has a positive and significant effect on performance. Discipline variable, competence and school culture to the performance influenced 69,5%. The remaining 30,5% is influence by other variables which is not included in the study. Key word : discipline, competence, performance and school culture. Â